2002
DOI: 10.1074/jbc.m104719200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Chondroitin 6-Sulfotransferase Gene in Relation to Lymphocyte Subpopulations, Brain Development, and Oversulfated Chondroitin Sulfates

Abstract: Chondroitin 6-sulfotransferase (C6ST) catalyzes the transfer of sulfate to position 6 of the N-acetylgalactosamine residue of chondroitin. To obtain direct evidence regarding the function of C6ST and its product, chondroitin 6-sulfate, in vivo, we isolated the mouse C6ST gene (C6st) and generated mice deficient in this gene (C6st ؊/؊ ) by embryonic stem cell technology. C6st؊/؊ mice were born at approximately the expected frequency and were viable through adulthood. In the spleen of C6st ؊/؊ mice, the level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
57
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 39 publications
1
57
0
1
Order By: Relevance
“…Study on knock-out mice provided insights of biosynthesis of oversulfated PGs in mice brain [13,40]. Our studies on bovine brain HS showed that it was more highly sulfated than standard bovine kidney HS [41].…”
Section: Discussionmentioning
confidence: 74%
“…Study on knock-out mice provided insights of biosynthesis of oversulfated PGs in mice brain [13,40]. Our studies on bovine brain HS showed that it was more highly sulfated than standard bovine kidney HS [41].…”
Section: Discussionmentioning
confidence: 74%
“…In the mouse, C6ST-1 was found in spleen and lung but also in eye, stomach, ovary, kidney, and, dependent on the developmental stage, in brain (17). Recently, the function of C6ST-1 has been further elucidated by inactivating CHST3 in the mouse (18). CHST3 Ϫ/Ϫ mice were born at the expected frequency and were viable through adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of Targeted ES Cells and Mice-Aliquots of 17 g of ScaIlinearized targeting vector DNA were electroporated into 1 ϫ 10 7 D3 ES cells (33), and homologously recombined cells were selected as described previously (34). The production of chimeric mice, which are derived from the targeted ES clones, was carried out as described previously (34).…”
Section: Methodsmentioning
confidence: 99%
“…The production of chimeric mice, which are derived from the targeted ES clones, was carried out as described previously (34). Chimeric male mice were bred with C57BL/6J mice.…”
Section: Methodsmentioning
confidence: 99%